Classification of Coal Quality Based on Proximate Analysis at CV. Bara Mitra Kencana to Meet the Requirements of Ombilin Power Plant - Ahmad Fadhly; Jevie Carter Putra; Rudy Anarta; Trisna Prima Sari S (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Coal quality and classification was essential, as coal served as an alternative energy resource for industry. Prior to utilization, coal quality and classification were analyzed through laboratory testing. One method that was applied was the proximate analysis based on ASTM D388 standards. This study used coal samples collected from three coordinate points at CV. Bara Mitra Kencana. The test results indicated variations in coal quality. Coal from this location was utilized as fuel for the Ombilin Steam Power Plant (PLTU), with a blending process carried out beforehand to improve the economic value of lower-quality coal. The coal quality received by PLTU Ombilin was recorded at 17.00%, with a significant improvement observed after blending. Based on laboratory analysis, the coal was classified as bituminous—high volatile A, which was generally caking in nature. The calorific value obtained was 14,316 Btu/lb for sample I, and 14,062 Btu/lb for samples II and III. These results demonstrated that the calorific value of coal from CV. Bara Mitra Kencana exceeded 14,000 Btu/lb, thereby meeting the quality standards required for power plant operations.